Laparoscopic distal pancreatectomy: better than open? - Fingerhut, Abe; Uranues, Selman; Khatkov, Igor; Boni, Luigi (Translational Gastroenterology and Hepatology, 2018)
Distal pancreatectomy is well suited to the laparoscopic approach. Laparoscopic distal pancreatectomy (LDP) provides the same postoperative recovery advantages reputed to minimal access surgery. However, there have been fears as to the safety of LDP in terms of life-threatening intra-operative events and post-operative complications, adequate carcinological outcomes as compared to traditional (open) distal pancreatectomy (ODP) when performed for cancer, as well as to whether the laparoscopic approach is well adapted to the variety of diseases that may affect the pancreas (ranging from trauma to benign or malignant disease) and whether the minimal access approach is well adapted to perform pancreatic surgery safely in the obese, the elderly or the frail. In this review of the literature, we sought to determine whether LDP was as safe, provided the same oncological outcomes and was applicable to all diseases involving the body and tail of the pancreas, and to particular patient characteristics, compared to the traditional open approach. Last we looked at cost issues. We concluded that this review of the literature allowed to state that laparoscopic distal pancreatectomy is feasible and safe for a wide range of diseases, both benign and malignant. Morbidity, mortality, and probably, also, carcinological outcomes are comparable to open surgery. The overall costs are similar but the advantages of minimal access surgery make it the preferred approach, once the surgical expertise is acquired and present.